Science, spirituality and the modernization of India - Paranjape, Makarand R., 1960- (London ; New York : Anthem Press, 2008)
Papers presented at the International Conference on Science and Spirituality in Modern India, held at New Delhi during 5-7 February 2006.
Science, spirituality and modernity in India -- Spiritual pilgrimage: Indian and Western perspectives; spirituality, logic and science -- Sir Sayyid Ahmed Khan and the modernization of South Asian Muslims -- Acharya Jagadish Chandra Bose: looking beyond the idiom -- Sri Aurobindo and Krishnachandra Bhattacharya on science and spirituality -- Chaos, complexity and emergence mechanisms: spiritual evolution in Sri Aurobindo and Teilhard de Chardin -- Science, spirituality and swaraj: towards a new aesthetics of ethical existence -- The concept of the Yuga: modern scientific approaches to bridge spiritual and philosophical concepts -- Sri Aurobindo's concept of evolution of consciousness: exploration through the paradigm of health and disease -- The blending of science and spirituality in the Ayurvedic tradition of healing -- Micro-sensing by Indian mystics -- The big picture for the science of consciousness -- Faith outside the lab -- The calling of practical spirituality -- Spiritual hysteria: a gendered perspective.
Includes bibliographical references.
Description based on print version record.
Keywords: Religion and science -- India -- History -- Congresses; Spirituality -- India -- History -- Congresses; RELIGION / General; Electronic books